2001
DOI: 10.1038/sj.jhh.1001209
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vascular disease and hypertension: a forgotten association?

Abstract: Peripheral vascular disease (PVD) is associated with a high cardiovascular morbidity and mortality. Intermittent claudication is the most common symptomatic manifestation of PVD, but is also an important predictor of cardiovascular death, increasing it by three-fold, and increasing all-cause mortality by two to five-fold. Hypertension is a common and important risk factor for vascular disorders, including PVD. Of hypertensives at presentation, about 2-5% have intermittent claudication, with this prevalence inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 76 publications
1
44
0
3
Order By: Relevance
“…However the prevalence of peripheral arterial disease equals to males after menopause. In our study the data shows that from 6 patients with peripheral arterial disease, males had increased prevalence 16 .…”
Section: Disscussionmentioning
confidence: 61%
See 3 more Smart Citations
“…However the prevalence of peripheral arterial disease equals to males after menopause. In our study the data shows that from 6 patients with peripheral arterial disease, males had increased prevalence 16 .…”
Section: Disscussionmentioning
confidence: 61%
“…In our study on patients of age between 45-65 years, it was found that prevalence was higher among patients with age greater than 65 years. Makin A et al (2002) in their study on sex prevalence, 512 patients were selected which comprised of equal number of males and females with hypertension. They found that there was a slight increase in number of cases of peripheral arterial disease in males than females.…”
Section: Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arterial hypertension is among the most important and most frequent cardiovascular disorders, in particular in the developing world. Hypertension is normally silent, asymptomatic and preventable, but if remained uncontrolled, it could progress into severe cardiovascular (Davies, 1991), cerebrovascular (Ogunniyi & Talabi, 2001), peripheral vascular (Makin et al, 2001) and neurodegenerative complications (Kivipelto et al, 2002). Regulation of hypertension is the result of a delicate balance between cardiac output and peripheral vascular resistance (Vikrant & Tiwari, 2001).…”
Section: Introductionmentioning
confidence: 99%